Avaliação da geração de resíduos sólidos provenientes de estabelecimentos comerciais e da disposição a pagar pelo manejo - Neves, Juliana Salomão das (2023)
This work evaluated the generation of waste from commercial establishments and generated services and willingness to pay (WTP) for the management of waste generated by such enterprises. For this, a wide systematic review of the literature was carried out, which allowed the identification not only of generation indicators, but also the comparison with those per capita residues of residues left automatically in Brazil. In addition, the pattern of commercial waste generation and service provision was verified in the field, as well as the WTP for managing these wastes, using the contingent valuation method and the city of Vitória/ES as a case study. From the systematic review, it was possible to identify that the main commercial typologies studied that do not concern the generation of solid waste are educational institutions, food services and accommodation, in addition to enabling the creation of a database of indicators of generation for several commercial typologies, obtained from the literature. When comparing the indicators with the mass collected per capita standard of municipal solid waste (RSM), an equivalence greater than 50% was found for educational institutions, accommodation services and food services, showing how these commercial typologies emerged for the generation of solid waste in a municipality. With the case study, it can be seen that only a third of those tolerated felt that they had to pay for the management of their waste, describing DAP greater than the heir by the municipality of Vitória/ES, with an average of R$ 0.10 per liter of solid handled. Due to the low adherence of those received, one can see the importance of identifying the main factors that influence DAP. As future work, it is suggested the construction of a representative econometric model, which allows not only to calculate the WTP in different scenarios, but also to relieve public power by transferring management ownership to large solid waste generators.